2000
DOI: 10.1161/01.atv.20.4.1061
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia pneumoniae –Reactive T Lymphocytes in Human Atherosclerotic Plaques of Carotid Artery

Abstract: Abstract-Linkage between Chlamydia pneumoniae infection and atherosclerosis has been confirmed in several studies, but the precise role of this organism in the disease process is not known. We investigated the relation and reactivity of T lymphocytes of human carotid plaques to C pneumoniae antigens. Tissue specimens were obtained from 17 patients who underwent carotid endarterectomy. Immunohistological staining and/or in situ hybridization revealed the presence of C pneumoniae in 11 (64%) of the 17 of the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 32 publications
(36 reference statements)
3
79
0
2
Order By: Relevance
“…However, these initial findings may help to elucidate in further studies mechanisms for development of EH. Since the interaction in the risk for EH of one allele of the HLA system (a key element of the immune response) and an infectious agent (C. pneumoniae) has been described in our study, the probability that immune and inflammatory mechanisms are important factors in the pathogenesis of EH (as has been well documented in atherosclerosis at the cellular 21 and biochemical level 22 ) is clearly higher than that previously suspected. On the basis of several experimental findings, [23][24][25][26][27][28] it has been hypothesized that chronic C. pneumoniae infection of the vessels may induce a chronic immune response orchestrated by cytokines and mediated by reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 50%
“…However, these initial findings may help to elucidate in further studies mechanisms for development of EH. Since the interaction in the risk for EH of one allele of the HLA system (a key element of the immune response) and an infectious agent (C. pneumoniae) has been described in our study, the probability that immune and inflammatory mechanisms are important factors in the pathogenesis of EH (as has been well documented in atherosclerosis at the cellular 21 and biochemical level 22 ) is clearly higher than that previously suspected. On the basis of several experimental findings, [23][24][25][26][27][28] it has been hypothesized that chronic C. pneumoniae infection of the vessels may induce a chronic immune response orchestrated by cytokines and mediated by reactive oxygen intermediates.…”
Section: Discussionmentioning
confidence: 50%
“…With a similar approach, Stemme et al (41) succeeded in isolating a plaque-derived CD4 ϩ clones specific to oxidized low-density lipoprotein. In contrast, other investigators used repeated stimulation with C. pneumoniae antigens and mitogens to expand plaque-infiltrating T cells, increasing the risk of in vitro artifacts in their analysis (42,43). Our data on the fine specificity of plaque-derived C. pneumoniae-specific clones showed a precise antigenic role for chlamydial OMP-2, HSP-10, and HSP-60.…”
Section: Figmentioning
confidence: 67%
“…[21][22][23][24][25][26] The finding of CD4 ϩ CD28 null cells reactive to hHSP60 during the acute phase of coronary artery disease and their absence in stable CSA and healthy individuals is of critical importance and suggests that an autoimmune T cell-mediated response may hold the balance. Although previous studies have reported the presence of HSP-reactive T cells within atheromatous lesions, 8 this is the first investigation into antigenic specificity of the CD4 ϩ CD28 null cells. The mechanism of emergence and outgrowth of these cells is unknown.…”
Section: Discussionmentioning
confidence: 91%